Strategies Used by English Teachers through Gamification at Secondary School: Strategi yang Digunakan oleh Guru Bahasa Inggris melalui Gamifikasi di Sekolah Menengah - Ummu Habibah Noersyaviqoh; Fika Megawati (Universitas Muhammadiyah Sidoarjo, 2025)
This study explores the strategies employed by an English teacher in conducting speaking activities in a secondary school setting. Using a qualitative research method, the research aims to understand the teaching approaches and techniques used by the teacher to enhance students’ effective speaking skills. Data was collected through classroom observations and in-depth interviews with the teacher, focusing on the implementation of various speaking activities designed to enhance student participation and communication. The research examines how teachers create an interactive and engaging learning environment that encourages students to speak English. The research provides insight into the practical application of speaking strategies in the classroom. It contributes to the wider field of language teaching and the development of speaking skills in secondary education.